Handbook of CALL Teacher Education and Professional Development Voices from Under-Represented Contexts - Tafazoli, Dara.; Picard, Michelle (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This comprehensive handbook provides an overview of current trends in computer-assisted language learning (CALL) teacher education and professional development across the globe. It highlights theories and practices in CALL teacher education and professional development in five sections, such as English language teaching, including pre-service teachers, in-service teachers, teacher educators, material developers, course designers and researchers. It explores the role of CALL teacher education and professional development in many underexplored countries such as Africa, Asia, Eastern Europe and the Middle East. It stresses the critical role of professional development programs, from the use of technology in its generic sense. The theoretical and empirical chapters in the book provide a more inclusive and comprehensive picture of various aspects of CALL teacher education and professional development globally. It offers context-specific approaches and strategies to language teachers and teacher educators. It provides pedagogical implications and suggestions for promoting digital literacy and autonomy in online education. This book provides valuable insights for researchers, teacher educators and teacher trainers in applied linguistics.
Contextualizing and Adapting Teacher Education and Professional Development -- CALL Teacher Education and Professional Development: Contextual Challenges in Under-Represented Contexts -- Pre-Service Chinese Foreign Language Teachers in Blended CALL Preparation Program: Case Study in Taiwan -- Secondary Pre-Service English Teachers' Response to CALL Innovation in Cambodia -- Fostering Digital Literacy and Learner Autonomy Readiness Among Pre-Service Teachers in Online Education -- Online Teacher Education in Times of Crisis: Listening to Teachers' Voices During COVID-19 -- How Do Indonesian EFL Student Teachers Solve Teaching Issues during Online Teaching Practicums? A Phenomenological Study -- CALL Teacher Education for Young Learner Classrooms -- Emergency Remote EFL Instruction in Brazil, China and Indonesia: What Teachers Learned and How -- Kimono Books and Chicken Hats: Doing Critical Literacy as Professional Development in One Urban Elementary School -- Teacher Education in Mobile Assisted Language Learning for Adult Migrants: A Study of Provincial Centres for Adult Education in Italy -- Emergency Online Teaching: Voices from Hong Kong CALL Teachers.
Keywords: Applied linguistics; Teachers -- Training of; Educational technology; Applied Linguistics; Teaching and Teacher Education; Digital Education and Educational Technology